Time-lapse analysis and morphokinetic evaluation of fresh vs. vitrified/warmed oocytes, including donor and explorative sibling oocyte cycles - Ramsay, Dylan (Stellenbosch : Stellenbosch University., 2020)
Thesis (MSc)--Stellenbosch University, 2020.